2017
DOI: 10.12788/jhm.2780
|View full text |Cite
|
Sign up to set email alerts
|

Use of Post‐Acute Facility Care in Children Hospitalized With Acute Respiratory Illness

Abstract: Children with RI who are most likely to use PAC have a high prevalence of multiple chronic conditions, multiple medications, and medical technology. Future investigations should assess the supply of PAC against the demand of hospitalized children with RI who might need it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Findings of increased readmission risk for those discharged home, when compared to post-acute care facilities, complements additional emerging evidence that these post-discharge health services, such as increased access to sub-acute and skilled nursing facilities, might help prevent subsequent acute-care hospitalizations in children with medical complexity, particularly in patients post-tracheotomy 10 . Previous studies have demonstrated that post-acute care use in pediatric patients is uncommon, even for CMC 21,28,29 . Additionally, Hispanic ethnicity has also been associated with decreased use of post-acute care facilities in pediatric patients 21,28,29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings of increased readmission risk for those discharged home, when compared to post-acute care facilities, complements additional emerging evidence that these post-discharge health services, such as increased access to sub-acute and skilled nursing facilities, might help prevent subsequent acute-care hospitalizations in children with medical complexity, particularly in patients post-tracheotomy 10 . Previous studies have demonstrated that post-acute care use in pediatric patients is uncommon, even for CMC 21,28,29 . Additionally, Hispanic ethnicity has also been associated with decreased use of post-acute care facilities in pediatric patients 21,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that post-acute care use in pediatric patients is uncommon, even for CMC 21,28,29 . Additionally, Hispanic ethnicity has also been associated with decreased use of post-acute care facilities in pediatric patients 21,28,29 . Our results may support future research to examine the association between availability and use of post-acute care facilities to prevent future bRTI hospital readmissions in this patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These children also have more visits to the Emergency Department than a well child [ 14 , 75 , 77 79 ]. This rate of attendance is often higher than the rates of attendance of elderly patients over 85 years of age [ 75 ]. Higher rates of visits are associated with greater distance from the hospital and being a younger child and having a large number of medications [ 24 , 80 – 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…They can have frequent clinic visits, are frequently hospitalised, and have a high risk of critical illness [5][6][7][74][75][76]. These children also have more visits to the Emergency Department than a well child [14,75,[77][78][79]. This rate of attendance is often higher than the rates of attendance of elderly patients over 85 years of age [75].…”
Section: Clinical Care Of the Childmentioning
confidence: 99%